X-Ray-based Kinematic Analysis of Cervical Spine According to Prosthesis Designs. Issue 5 (June 2015) - Park, Sung B.; Kim, Ki J.; Jin, Yong J.; Kim, Hyun J.; Jahng, Tae-A.; Chung, Chun K.
<x xml:space="preserve">Abstract</x> Study Design: A retrospective study. Objective: To identify significant kinematic changes in the cervical spine after cervical artificial disk replacement (ADR) using prostheses with diverse designs. Summary of Background Data: Various types of artificial disks are used for cervical ADR. However, few clinical studies with a follow-up of 2 or more years have reported on the change in the curvatures and range of motion (ROM) of the cervical spine after cervical ADR in relation to different designs. Methods: The cohort comprised 58 patients who underwent single-level cervical ADR for radiculopathy. The patients were divided into 4 groups according to the device they received: Mobi-C, Bryan, PCM, and Prestige LP. The radiographs of the cervical spine were obtained preoperatively and at 12, 24, and 36 months after surgery. Several kinematic parameters, including lordotic angles and ROM of the cervical spine, index level, and superior and inferior adjacent disk levels, were assessed preoperatively and at predefined follow-up time points. Results: Cervical sagittal lordosis in patients who received Bryan and PCM prostheses increased at the last follow-up period. The 4 patient groups showed a trend toward an increase of lordosis in the superior adjacent segment with time. The patients who received the Bryan device lost their preoperative lordotic angle at the inferior adjacent level. The ROM of the cervical spine in patients who received Bryan and PCM prostheses increased at the last follow-up compared with preoperative values. The incidence of adjacent segment degeneration in the Mobi-C, Bryan, Prestige LP, and PCM groups were 14.2%, 25%, 9.0%, and 7.6%, respectively. Conclusions: These results suggest preservation of sagittal ROM and increased superior adjacent segment kinematics, regardless of prosthesis design. Devices with an unconstrained design may not be beneficial to adjacent segment kinematics compared with semiconstrained prostheses.